Corporate Governance, Profitability And Firm Value: A Systematic Literature Review - Kharimah Murni; Enggar Diah Puspa Arum; Wiralestari (International Journal of Economics, Business and Innovation Research, 2025)
This study conducts a systematic literature review combined with bibliometric analysis to map the intellectual landscape, conceptual development, and research trends surrounding Corporate Governance, Profitability, and Firm Value within contemporary academic scholarship. Using the PRISMA framework, peer-reviewed articles published up to November 2025, written in English, and indexed in the Scopus database were rigorously identified, screened, and synthesized. Bibliometric techniques using VOSViewer were applied to visualize citation structures, co-authorship networks, and keyword co-occurrence patterns, enabling a comprehensive understanding of the field’s thematic evolution. The review reveals that scholarly interest in the nexus between corporate governance mechanisms, profitability indicators, and firm value has grown substantially over the past decade. However, the research stream remains dispersed across varying methodological approaches and is dominated by specific corporate governance constructs, such as board characteristics and ownership structure. Influential authors, dominant themes, and existing research gaps are identified, underscoring the need for deeper theoretical integration, stronger causal designs, and broader cross-country comparisons. The combined methodology of systematic review and bibliometric mapping provides a robust analytical foundation, clarifying the trajectory of the field and offering direction for future empirical and conceptual contributions to corporate governance and value-creation research.